Effect of Papaver rhoeas extract on in vitro maturation and developmental competence of immature mouse oocytes - Golkar‐Narenji, Afsaneh (Reprod Med Biol, 2010)
PURPOSE: This experiment examined the effect of Papaver rhoeas L. extract on in vitro maturation, in vitro fertilization (IVF) and subsequent developmental competence of mouse oocytes. MATERIALS AND METHODS: Cumulus oocyte complexes (COCs) at germinal vesicle stage were collected from female Naval Medical Research Institute (NMRI) mouse ovaries. The COCs were transferred to maturation medium supplemented with different concentrations of P. rhoeas extract. Two trials were carried out to examine the effect of low concentrations (0, 10, 15, 20, 25 μg/ml) and high concentrations (0, 50, 100, 200 μg/ml) of the extract. The maturation rate was recorded. After IVF, embryos were cultured and their developmental process was monitored for 96 h. RESULTS: Maturation rate and blastocyst formation improved by using low concentrations of the extract; however, no significant increase was observed when compared to the control group. In addition no significant differences were observed in the fertilization rates of oocytes treated with both low and high concentrations compared to the control group. However, among higher concentrations, 100 μg/ml, P. rhoeas extract significantly increased both the in vitro maturation rate and in vitro developmental (IVD) competence when compared to the control group (P < 0.05). CONCLUSIONS: It was concluded that natural extracts increase the IVD competence of oocytes. The improved effect on oocyte maturation was dependent on the addition of optimum concentrations of P. rhoeas extract to the maturation medium.